(untitled) (Journal of Asian Development Studies, 2018)
Globally, about 90% of the poor people of developing world lived in Asia or Africa. Three of every four poor people in developing countries live in rural areas and 2.1 billion living on less than 2 a day and 880 million on less than 1 a day and mostly people depends on agriculture for their livelihoods. Poverty is totally out of control in the rural areas of the Pakistan, where people are in a state of deficiency with regards to incomes, clothing, housing, health care and education facilities. According to economics survey 2011-12, more than 63 percent of the population living in rural areas and depends on agriculture for their livelihood. Agriculture sector contributes in GDP is around 22 percent while it provides employment at least more than 40 percent of the total population. The study analyze the determinants of Poverty in case of Pakistan extracting 31 time series annually observations. The study employed Johansen co integration methodology to test for the existence of a long run relationship between variables. The co integrating regression as far as this considers only the long run property of the model, and does not deal with short run dynamics explicitly. For this, the error correction mechanism is used. The study concluded that all the variables have negative and significant effect on poverty while inflation has positive and significant effect on Poverty.